2009
DOI: 10.1080/09511920802209033
|View full text |Cite
|
Sign up to set email alerts
|

Hedging production schedules against uncertainty in manufacturing environment with a review of robustness and stability research

Abstract: Scheduling is a decision-making process that is concerned with the allocation of limited resources to competing tasks (operations of jobs) over a time period with the goal of optimising one or more objectives. In theory, the objective is usually to optimise some classical system performance measures such as makespan, tardiness/earliness and flowtime under deterministic and static assumptions. In practice, however, scheduling systems operate in dynamic and stochastic environments. Hence, there is a need to inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 35 publications
0
61
0
3
Order By: Relevance
“…Este trabajo toma como referencia principalmente los trabajos de Lei, Verderame, Sabuncuoglu y Zukui, desarrollados en [19], [25] , [33] y [40]. En "Scheduling bajo incertidumbre", se menciona el concepto, y la finalidad del scheduling así como la importancia de considerar la incertidumbre.…”
unclassified
“…Este trabajo toma como referencia principalmente los trabajos de Lei, Verderame, Sabuncuoglu y Zukui, desarrollados en [19], [25] , [33] y [40]. En "Scheduling bajo incertidumbre", se menciona el concepto, y la finalidad del scheduling así como la importancia de considerar la incertidumbre.…”
unclassified
“…that must be captured and responded effectively, namely timely and appropriately [2]. However, the difficulty of addressing the issue of uncertainty in dynamic manufacturing environments is well recognized by researchers and practitioners for many decades [3][4][5]. Hence, this study questions: What important factors have been identified in literature to handle the unexpected events effectively and what insights can we get from companies, regarding the event handling process and identified factors?…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such studies include [17,[20][21][22]32]. We refer the reader to [4,14,27] for detailed reviews of the studies that endeavor to cope with unforeseen disruptions and uncertainties.…”
Section: Introductionmentioning
confidence: 99%